The impact of initial planning activities on project success: Some evidence from a study of Japanese companies - Christoph Stockstrom; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2006)
The domain of New Product Development (NPD) is subject to considerable uncertainties. However, companies are required to manage the innovation process as efficiently as possible. The resulting conflicting demands often leave companies struggling to achieve both, efficiency as well as flexibility due to their often opposing implications for organizing and managing NPD projects. In this context, planning plays a central role. This study tries to develop a deeper understanding of the influences of project planning, the degree of technological newness and both their effects on project success. Our analysis is based on project planning of in combination with New Product Development projects in 497 electrical and mechanical engineering companies.
Keywords: 650